Hardware-based efficiency advances in the EXA-DUNE project - Bastian, Peter; Ippisch, Olaf; Müthing, Steffen (Software for Exascale Computing - SPPEXA 2013-2015, 2016)
We present advances concerning efficient finite element assembly and linear solvers on current and upcoming HPC architectures obtained in the frame of the Exa-Dune project, part of the DFG priority program 1648 Software for Exascale Computing (SPPEXA). In this project, we aim at the development of both flexible and efficient hardware-aware software components for the solution of PDEs based on the DUNE platform and the FEAST library.